Country music at university: Identity translations in students' cultural consumption (Intercom - Brazilian Journal of Communication Sciences, 2026)
This article aims to contextualize country music and reflect on it as a massive popular phenomenon ingrained in national culture, from the perspective of a group of university students from Goiânia (GO) and Campo Grande (MS). The analysis has enabled us to perceive both diachronic connections in the resignifications of the country genre by the media industry and hegemonic structural changes in the last 100 years in this country. In order to contribute to this problematization, we have intertwined studies on cultural identities by Hall (2003), Martín-Barbero (2001), García-Canclini (2013) and Oliven (2006); socio-historical references by Cândido (1964), Ribeiro (1995) and Yatsuda (1987); and identity translations that have been made explicit in the reports of the group of interviewees in the research.
Keywords: sertanejo music; sertanejo music in the media; cultural identifications; music consumption.